My first book of time - Llewellyn, Claire (Boston, Mass. : Distributed by Houghton Mifflin, 1992)
Explains how to tell time and discusses such aspects of time as day and night, days of the week, and months of the year. Includes a fold-out clock face for practice.
"Recommended for children aged four years and up"--T.p. verso.
Keywords: Clocks and watches -- Juvenile literature; Time -- Juvenile literature; Toy and movable books -- Specimens; Clocks and watches; Time; Toy and movable books